THE IMPACT OF ARTIFICIAL INTELLIGENCE ON LANGUAGE LEARNING - Nazirova Xilola Ro‘zaliyevna (Ustozlar uchun, 2025)
Abstract: Artificial Intelligence (AI) has revolutionized the landscape of education, particularly in the field of language learning. This paper explores the ways in which AI-driven tools—such as intelligent tutoring systems, machine translation, chatbots, and adaptive learning platforms—enhance language acquisition. It also discusses the challenges and ethical considerations of AI integration and its future potential in shaping personalized, accessible, and efficient language education globally.